2000
DOI: 10.1074/jbc.275.2.1201
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided Transformation of Charybdotoxin Yields an Analog That Selectively Targets Ca2+-activated over Voltage-gated K+ Channels

Abstract: We have used a structure-based design strategy to transform the polypeptide toxin charybdotoxin, which blocks several voltage-gated and Ca 2؉ -activated K ؉ channels, into a selective inhibitor. As a model system, we chose two channels in T-lymphocytes, the voltagegated channel Kv1.3 and the Ca 2؉ -activated channel IKCa1. Homology models of both channels were generated based on the crystal structure of the bacterial channel KcsA. Initial docking of charybdotoxin was undertaken with both models, and the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 36 publications
3
108
0
Order By: Relevance
“…These biophysical parameters are in good agreement with those reported earlier for Kv1.3 channels (28,34,35). Pharmacological characterization of the current also supported this assumption: the sensitivity of the current to MgTx (dissociation constant, K d ϭ 50 Ϯ 12 pM, n ϭ 3), charybdotoxin (3.4 Ϯ 0.6 nM, n ϭ 3), and tetraethylammonium (14 Ϯ 1 mM, n ϭ 4), was similar to that of Kv1.3 expressed in lymphocytes (35)(36)(37). Based on the pharmacological and biophysical properties of the cells we concluded that CTLs express Kv1.3 channels.…”
Section: Hla-a2-specific Killing Of Target Cells By Allogen-activatedsupporting
confidence: 67%
“…These biophysical parameters are in good agreement with those reported earlier for Kv1.3 channels (28,34,35). Pharmacological characterization of the current also supported this assumption: the sensitivity of the current to MgTx (dissociation constant, K d ϭ 50 Ϯ 12 pM, n ϭ 3), charybdotoxin (3.4 Ϯ 0.6 nM, n ϭ 3), and tetraethylammonium (14 Ϯ 1 mM, n ϭ 4), was similar to that of Kv1.3 expressed in lymphocytes (35)(36)(37). Based on the pharmacological and biophysical properties of the cells we concluded that CTLs express Kv1.3 channels.…”
Section: Hla-a2-specific Killing Of Target Cells By Allogen-activatedsupporting
confidence: 67%
“…ChTx is known to block Ca 2+ -activated KCa1.1 and KCa3.1 channels and specific Kv1.x channels (7,20). KCa3.1 channels are apamin-insensitive but have specific binding sites for ChTx and the clotrimazole-related compound TRAM-34 (9,21). TRAM-34 has been established as a selective KCa3.1 blocker with no effects on KCa1.1, KCa2.2, or a wide array of Kv channels (9,10) or Cav3 channels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This value, selected from other pairwise experiments (22), is 2-fold higher than the minimal threshold value characterizing interacting residues separated by 4-7 Å (18). Table 3, which is published as supporting information on the PNAS web site, www.pnas.org, and the histogram in Fig 3 show ⌬⌬G int values derived from our pairwise experiments.…”
Section: Double-mutant Cyclementioning
confidence: 99%